ANALISIS MANAJEMEN RISIKO PASIEN JATUH DI INSTALASI RAWAT INAP RSIA XYZ JAKARTA TIMUR - Umina, Rani; Permanasari, Vetty Yulianty (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2023)
The incidence of patients fall is a second big issue after the incidence of medication errors. Reducing the risk of falls is one measure of service quality that is the main focus of the Hospital. This study aims to analyze the risk management of inpatient falls at Woman and Children Hospital SMB in 2020 by using FMEA tool. This research is a qualitative study by using in-depth interviews, observation, document review, and FGD as data collection methods. The results of this study indicate that factors of patient fall which become high priority potential failure modes are found in the structure and process variables. Factors in the structure variables include hospital protocols that do not regulate the mobilization of discharged patients and infrastructures that have not been provided. Factors in the process variable include inconsistent documentation and patient supervision. The potential impacts are difficulty to measure risk management of patient fall and increased risk of patient fall. Research recommendations are strengthening the monitoring system through the implementation of bedside checklist status, shift reports on patient needs related to falling prevention, optimization briefings and de-briefings of patient Safety, and improving the SOP of discharge planning.